Anti‐Mullerian Hormone as Predictor of Future and Ongoing Bone Loss During the Menopause Transition. (4th April 2022) - Karlamangla, Arun S; Shieh, Albert; Greendale, Gail A; Yu, Elaine W; Burnett‐Bowie, Sherri‐Ann M; Sluss, Patrick M; Martin, Deborah; Morrison, Anthony; Finkelstein, Joel S
ABSTRACT: The menopause transition in women is a period of significant bone loss, with rapid declines in bone mineral density (BMD) commencing a year before the final menstrual period (FMP). Changes in menstrual bleeding patterns cannot reliably tell us if this rapid bone loss has begun or is imminent. We hypothesized that low circulating levels of anti‐Mullerian hormone (AMH), which decline as women approach the FMP, would be associated with future and ongoing rapid bone loss. We used data from The Study of Women's Health Across the Nation, a multisite, multi‐ethnic, prospective cohort study of the menopause transition to test this hypothesis. Adjusted for age, body mass index, race/ethnicity, and study site, every 50% decrement in AMH level in premenopause and early perimenopause was associated with 0.14% per year faster decline over the following 3 to 4 years in lumbar spine BMD and 0.11% per year faster decline in femoral neck BMD ( p  < 0.001 for both). AMH in late perimenopause was not associated with the rate of future BMD decline. AMH was also associated with the magnitude of ongoing bone loss, measured as percent of peak BMD lost by the end of the next 2 to 3 years. Every 50% decrement in AMH level was associated with 0.22% additional loss in spine BMD in premenopause, 0.43% additional loss in early perimenopause, and 0.50% additional loss in late perimenopause ( p  < 0.001 for all three). If a woman will lose more of her peak BMD than the site‐specific least significant change (LSC) at either the lumbar spine or femoral neck by the next 2 to 3 years, then AMH below 100 pg/mL will detect it with sensitivity of 50% in premenopause, 80% in early perimenopause, and 98% in late perimenopause. These findings suggest that AMH measurement can help flag women at the brink of significant bone loss for early intervention. © 2022 American Society for Bone and Mineral Research (ASBMR).